Effective profit taxation and the elasticity of the corporate income tax base: evidence from German corporate tax return data - Nadja Dwenger; Viktor Steiner (Deutsches Institut für Wirtschaftsforschung (DIW), 2008)
We estimate the elasticity of corporate taxable income with respect to the effective corporate tax rate on the basis of a pseudo-panel constructed from corporate tax return micro data for the period 1998-2001, a period which saw the introduction of a major corporate tax reform in Germany. Endogeneity of the effective tax rate is controlled for by an instrumental variable approach. Our instrument for the observed effective corporate tax rate is the counterfactual effective tax rate a corporation would face in a particular period had there be no endogenous change of corporate profits. This counterfactual is obtained from a detailed microsimulation model of the corporate sector based on tax return micro data. We find a statistically significant and relatively large point estimate of the average tax base elasticity, which implies that a reduction of the statutory corporate tax rate would reduce corporate tax receipts less than proportionally due to income shifting activities. We also find some statistically weak evidence for the hypothesis that the tax base elasticity is higher for corporations that may benefit from various forms of tax shields.
Keywords: H32; H21; F23; C15; 330; Corporate income taxation; tax base elasticity; micro simulation; Körperschaftsteuer; Unternehmensbesteuerung; Steuerbemessung; Steuertarif; Elastizität; Mikrosimulation; Deutschland